汉语“春”成语的含义与文化价值分析 - Annisa Maulina; Lily Thamrin; Bun Yan Khiong (Universitas Tanjungpura, 2022)
AbstractMandarin idioms are fixed phrases used in Mandarin for a long time and the source is abundant. But, there are differences in environment and perspective in Indonesia and China.Therefore, by analyzing idioms containing spring, we learn mandarin while understanding its cultural value. The research takes mandarin idioms containing the Chinese character “春”（read: Chun） as the object of research. The research method used descriptive qualitative. Through the analysis method, the writer can make a conclusion that in terms of its meanings and emotional color, the most emotional color of the Chinese character “春”（read: Chun) mandarin idioms are that it contains praise. From the perspective of cultural values, the Chinese character “春”（read: Chun) mandarin idioms include teaching methods, expressing the customs and conditions of the Spring Festival, enjoying the spring scenery, the love of children for their parents, traditional architectural culture, characteristics between spring and autumn, then etiquette to become a good ruler.Keywords: Chinese Idiom, Cultural Values, Emotional Color , Meaning, Spring